2016
DOI: 10.1097/qad.0000000000001193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geographic origin, sex, and HIV transmission group on the outcome of first-line combined antiretroviral therapy in France

Abstract: Compared with FRA MSM, all migrants had a lower likelihood of CD4 cell recovery, and nonhomosexual men had a higher likelihood of negative virological and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In addition to the factors mentioned above, older age, male sex, lower nadir CD4 T‐cell counts, lower CD4/CD8 ratios, and a lower naïve/memory CD4 + T‐cell ratio have been associated with a blunted immunological response to ART treatment. Ethnic origin is also associated with immune recovery . Furthermore, host genetic factors, metabolic characteristics, and specific ART regimens may play a role in incomplete immune recovery.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the factors mentioned above, older age, male sex, lower nadir CD4 T‐cell counts, lower CD4/CD8 ratios, and a lower naïve/memory CD4 + T‐cell ratio have been associated with a blunted immunological response to ART treatment. Ethnic origin is also associated with immune recovery . Furthermore, host genetic factors, metabolic characteristics, and specific ART regimens may play a role in incomplete immune recovery.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…Ethnic origin is also associated with immune recovery. [171][172][173][174] Furthermore, host genetic factors, metabolic characteristics, and specific ART regimens may play a role in incomplete immune recovery. Luo…”
Section: Other Factors Associated With Immune Reconstitutionmentioning
confidence: 99%
“…After adjustment, migrants from SSA were half as likely to have virological suppression on cART as other individuals. Previous studies have found lower virological response rates in migrants from SSA than in nonmigrants, mainly in men [3,6,7]. Similarly, socioeconomic factors and lifestyle factors, which could explain some differences in adherence between migrants, especially migrants from SSA, and natives or people from Western Europe [17][18][19], were not recorded.…”
Section: Discussionmentioning
confidence: 96%
“…In high-income countries, HIV-infected adults with controlled infection and high CD4 cell counts currently live longer than ever before [ 1 ], and the main causes of morbidity and mortality have switched from AIDS-defining to non-AIDS-defining disorders [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. In western European countries, despite experiencing more AIDS-defining events [ 10 , 11 ], migrants from sub-Saharan Africa (SSA) have lower mortality than non-migrants, mainly owing to lower non-AIDS mortality [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In western European countries, despite experiencing more AIDS-defining events [ 10 , 11 ], migrants from sub-Saharan Africa (SSA) have lower mortality than non-migrants, mainly owing to lower non-AIDS mortality [ 12 ]. In France, heterosexual migrant men originating from SSA and non-French West Indies (NFW), and non-migrant men, have a higher risk of new AIDS-defining events, serious non-AIDS events or death after cART initiation than non-migrant men who have sex with men (MSM), while this is not the case of women [ 9 ]. This latter study compared heterosexual individuals to MSM, two groups with different socioeconomic and lifestyle factors, and specific causes of morbidity were not assessed.…”
Section: Introductionmentioning
confidence: 99%